Atividade in vitro de Pleurotus ostreatus, Pleurotus florida e Pleurotus djamor em ovos de ciatostomíneos de equinos - Giacometi, Marjorie de (2020)
Brazil has the third largest herd of horses in the world, with 5 million heads, generating approximately US $ 7.5 billion per year and consequently using direct. For this reason, it is important to maintain the health and well being of these animals. However, parasitic diseases in horses delay their development and may lead the animal to death, causing serious economic losses. The anti-helminth resistance installed in several herds is a serious problem in veterinary medicine, since antiparasitic treatments do not have the expected effect on these infections or cause high toxicity in the animal. The fungus Pleurotus spp., known worldwide as “oyster mushroom”, an edible mushroom, has over 1000 species already described. It is known that this fungus is capable of producing bioactive compounds that help to combat pathologies and improve the well-being of people, in addition to being considered a nematophagous fungus capable of producing toxins effective in the control of various parasites. The object of this study was to evaluate the activity of different species of Pleurotus spp. in vitro on naturally infected equine cyathostomes eggs. In search of this, the aqueous extract of Pleurotus ostreatus, Pleurotus florida and Pleurotus djamor were used. Eggs were recovered and incubated (27 ° C) along with extracts at increasing concentrations of 0.62%, 1.25%, 2.5%, 5%, 10% and a negative control group with distilled water. The reading was done in 48h in inverted microscope. All concentrations showed effects on hatchability. It was observed that P. florida was more effective than the other Pleurotus, inhibiting hatchability by up to 92.19% at the highest concentration (10%), with LC50 of 2.13% (± 0.12), while inhibition P. ostreatus was 55.46%, coLC50 7.44% (± 0.09), while P. djamor 23.67% at the same concentration. The use of this fungus against cyathostomines shows great potential as a biological control of the nematode.